2011 International Conference on Process Automation, Control and Computing 2011
DOI: 10.1109/pacc.2011.5978960
|View full text |Cite
|
Sign up to set email alerts
|

Estimation, Analysis and Smoothing of Self-Similar Network Induced Delays in Feedback Control of Nuclear Reactors

Abstract: Abstract-This paper analyzes a nuclear reactor power signal that suffers from network induced random delays in the shared data network while being fed-back to the Reactor Regulating System (RRS). A detailed study is carried out to investigate the self similarity of random delay dynamics due to the network traffic in shared medium. The fractionality or selfsimilarity in the network induced delay that corrupts the measured power signal coming from Self Powered Neutron Detectors (SPND) is estimated and analyzed. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This typical case is known as non-Gaussianα -stable distribution of the random variable which makes the mathematically tractable solutions for suppression of such stochastic phenomena with fractional order characteristics quite difficult [43]. Figure 7 shows that the run-time variance of such spiky random variables (packet delays) does not converge to a finite value and have a non-Gaussianα -stable distribution [42].…”
Section: Fuzzy Fopid Controller Design With Stochastic Phenomena In Tmentioning
confidence: 99%
See 2 more Smart Citations
“…This typical case is known as non-Gaussianα -stable distribution of the random variable which makes the mathematically tractable solutions for suppression of such stochastic phenomena with fractional order characteristics quite difficult [43]. Figure 7 shows that the run-time variance of such spiky random variables (packet delays) does not converge to a finite value and have a non-Gaussianα -stable distribution [42].…”
Section: Fuzzy Fopid Controller Design With Stochastic Phenomena In Tmentioning
confidence: 99%
“…The random network induced delay consideration has been motivated from the study reported in [42]. Majumder et al [42] used various smoothing filters for removing the stochastic nature of the power signal which is continuously fed back from the reactor house to the RRS through a long communication medium.…”
Section: Fuzzy Fopid Controller Design With Stochastic Phenomena In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…De-noising detector data using different types of wavelets was carried out for a particular case of Self Powered Neutron Detector (SPND) where the signal was presumed to be corrupted (Majumder et al, 2011a). Minimizing the effect of randomness in the reactor power transient data by using different classes of smoothing was investigated in feedback control of a large Pressurized Heavy Water Reactor (PHWR) (Majumder et al, 2011b(Majumder et al, , 2012 along with other work related to investigation and minimization of sensor noise with respect to reactor control (Das et al, 2011(Das et al, , 2013.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For cases when the smooth width is very large or signal distortion is highly undesirable, the Savitzky-Golay (Majumder et al, 2011b) algorithm can be applied. This method is based on the principle of least-square fitting of polynomials to segments of the data.…”
Section: Principles Of Operation -Conventional Low-pass Filtersmentioning
confidence: 99%